Branding Produk UMKM Kampung Wisata Bisnis Tegal Waru melalui Reputasi Merek dan Basis Informasi Teknologi - Endang Purwaningsih; Suhaeri Suhaeri; Evie Rachmawati Nur Ariyanti (Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 2020)
The objectives of this program are increasing the competence of producers in the product business link by facilitating the formation of legal entities, legal protection of brands expanding internet marketing networks (online), and improving marketing management competencies. The method of approach is to conduct training and mentoring continuously until it is independent. The results of this activity Tegal Waru SMEs want to optimize the role of BUMDES, so there is no need to create an UMKM association, want to have a trademark and compare with e commerce that has been provided by the team. It is expected that turnover will increase, more than 20 percent. In the previous year's mono PKM the turnover had increased by 20 percent, so in 2019-2020 it was targeted to increase by 25 percent. How to cite:Purwaningsih, E., Suhaeri, Ariyanti, E. R. N. (2020). Branding Produk UMKM Kampung Wisata Bisnis Tegal Waru melalui Reputasi Merek dan Basis Informasi Teknologi. Abdimas: Jurnal Pengabdian Masyarakat Universitas Merdeka Malang, 5(1), 60-69.DOI: https://doi.org/10.26905/abdimas.v5i1.3392